Effect of phosphorus deficiency on reflectance and chlorophyll fluorescence of cotyledons of oilseed rape (Brassica napus L.) - Yaryura, Pablo Marcelo (2009)
The spectroscopic changes in reflectance and fluorescence caused by phosphorus (P) starvation in Brassica napus L. young plants were evaluated. P deficiency produced an important decrease in reflectance values between 500 and 650 nm for both intact leaves and cotyledons. Furthermore, cotyledons under P deficiency showed a Chl-F ratio in the red/far-red region (Fred/ Ffar-red) lower than that of non-stressed plants (1.91 and 2.89 respectively). As minimal differences in Fred/Ffar-red were detected in leaves, P deficiencies may be better perceived by measuring changes in Chl-F emission in cotyledons than in leaves. Stressed cotyledons also showed different emission spectra in the blue green (maxima at 470 and 560 nm) from those of non-stressed cotyledons. The results are explained in terms of higher anthocyanin and chlorophyll contents and of damage to photosystem II. We evaluate that measuring variations in fluorescence and reflectance data may be useful to detect early damages induced by P stress. © 2009 Blackwell Verlag.